Alarming attrition rates among HIV-infected individuals in pre-antiretroviral therapy care in Myanmar, 2011-2014 - Myo Minn Oo; Vivek Gupta; Thet Ko Aung; Nang Thu Thu Kyaw; Htun Nyunt Oo; Ajay MV Kumar (Taylor & Francis Group, 2016)
Background: High retention rates have been documented among patients receiving antiretroviral therapy (ART) in Myanmar. However, there is no information on human immunodeficiency virus (HIV)-infected individuals in care before initiation of ART (pre-ART care). We assessed attrition (loss-to-follow-up [LTFU] and death) rates among HIV-infected individuals in pre-ART care and their associated factors over a 4-year period. Design: In this retrospective cohort study, we extracted routinely collected data of HIV-infected adults (>15 years old) entering pre-ART care (June 2011-June 2014) as part of an Integrated HIV Care (IHC) programme, Myanmar. Attrition rates per 100 person-years and cumulative incidence of attrition were calculated. Factors associated with attrition were examined by calculating hazard ratios (HRs). Results: Of 18,037 HIV-infected adults enrolled in the IHC programme, 11,464 (63%) entered pre-ART care (60% men, mean age 37 years, median cluster of differentiation 4 (CD4) cell count 160 cells/µL). Of the 11,464 eligible participants, 3,712 (32%) underwent attrition of which 43% were due to deaths and 57% were due to LTFU. The attrition rate was 78 per 100 person-years (95% CI, 75-80). The cumulative incidence of attrition was 70% at the end of a 4-year follow-up, of which nearly 90% occurred in the first 6 months. Male sex (HR 1.5, 95% CI 1.4-1.6), WHO clinical Stage 3 and 4, CD4 count <200 cells/µL, abnormal BMI, and anaemia were statistically significant predictors of attrition. Conclusions: Pre-ART care attrition among persons living with HIV in Myanmar was alarmingly high - with most attrition occurring within the first 6 months. Strategies aimed at improving early HIV diagnosis and initiation of ART are needed. Suggestions include comprehensive nutrition support and intensified monitoring to prevent pre-ART care attrition by tracking patients who do not return for pre-ART care appointments. It is high time that Myanmar moves towards a 'test and treat' approach and ultimately eliminates the need for pre-ART care.